¿Cazabobos o Salvavidas? : La Economía Política de los Fotorradares en Chile - Paredes, Ricardo; Rizzi, Luis; Valenzuela, Javier (Estudios de Economía, 2016)
Most road accidents in Chile (causing about 1,600 deaths per year) are linked to speeding. A widely used control mechanism all over the world, the speed detectors, enabled in the middle of the 1990’s was then suddenly prohibited in Chile through the enactment of a law justified on the idea that radars were only used to raise funds to local governments and in some way, a source of illegal profits. This paper studies the causes and consequences of this law. In particular, it attempts to verify whether the evidence is more consistent with the hypothesis that speed detectors radars were used as cazabobos or, on the contrary, they were effective reducing accidents and their consequences. We conclude that the evidence is consistent with the second hypothesis, so that such a law caused important social costs. Depending on the life valuation method considered, and projecting the evidence of some road areas to only two Santiago districts, we conclude that the cost of the law ranges between US$83 and US$ 600 millions in present value for those districts. The effect of a widely applied speed detector program is expected to be much more convenient.